2005
DOI: 10.1098/rspb.2005.3078
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio strategies and the evolution of cue use

Abstract: Quantitative tests of sex allocation theory have often indicated that organism strategies deviate from model predictions. In pollinating fig wasps, Lipporrhopalum tentacularis, whole fig (brood) sex ratios are generally more female-biased than predicted by local mate competition (LMC) theory where females (foundresses) use density as a cue to assess potential LMC. We use microsatellite markers to investigate foundress sex ratios in L. tentacularis and show that they actually use their clutch size as a cue, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 46 publications
5
62
2
Order By: Relevance
“…The determination of cue use patterns in such species is of general importance to evolutionary biologists because of its implications for our understanding of whether there are constraints upon the precision of adaptation (see also Herre 1987;West & Herre 1998;Herre et al 2001). Deviations in fit from the quantitative predictions of classical LMC theory (see Hamilton 1967) have been hypothesized to be a consequence of foundresses using cues other than Moore et al 2005). Of course, with regard to whether adaptation is constrained, this means the question becomes how closely foundress strategies approximate theoretical optima for a given clutch size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The determination of cue use patterns in such species is of general importance to evolutionary biologists because of its implications for our understanding of whether there are constraints upon the precision of adaptation (see also Herre 1987;West & Herre 1998;Herre et al 2001). Deviations in fit from the quantitative predictions of classical LMC theory (see Hamilton 1967) have been hypothesized to be a consequence of foundresses using cues other than Moore et al 2005). Of course, with regard to whether adaptation is constrained, this means the question becomes how closely foundress strategies approximate theoretical optima for a given clutch size.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al's (2005) model predicts that such foundresses should exhibit a negative logarithmic relationship between clutch size and sex ratio. Hence, to maintain the optimal sex ratio as clutch size increases, they should produce mostly male offspring at the start of oviposition bouts, followed by mostly females with a few males interspersed (see also Stubblefield & Seger 1990).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study where the focus was on sex ratio (Kjellberg et al 2005), we found no evidence for females leaving figs and we believe that the foundresses were overlooked in the Ware & Compton (1992) study cited by Moore et al (2003). When not all females contribute to the brood, or do so in unequal proportions, the optimal sex ratio is more female biased than with equal contributions (Frank 1985;Moore et al 2005). Below, we use data showing higher than expected sex ratios to argue that overcounting is not likely to be a problem, and if it is, it seems unlikely that there will be a systematic difference between fighting and nonfighting species.…”
mentioning
confidence: 79%